2020
DOI: 10.1007/s11412-020-09322-6
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the participation and social dimensions of computer-supported collaborative learning through social network analysis: which method and measures matter?

Abstract: The increasing use of digital learning tools and platforms in formal and informal learning settings has provided broad access to large amounts of learner data, the analysis of which has been aimed at understanding students' learning processes, improving learning outcomes, providing learner support as well as teaching. Presently, such data has been largely accessed from discussion forums in online learning management systems and has been further analyzed through the application of social network analysis (SNA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 60 publications
(127 reference statements)
2
27
0
1
Order By: Relevance
“…For instance, the use of community analytics (Klamma 2013;Jeong et al 2017) could contribute to guide further analyses of the Go-Lab community focusing on the teachers themselves, how they move from individual to collaborative interactions, and how these interactions develop over time (Imroz 2019). From a network analysis point of view, integrating social network analysis (Jan et al 2019;Saqr et al 2020), social learning analytics (Shum and Ferguson 2012), and cluster analysis could help us understand the social practices and the role that experts play in them (Martínez et al 2006;Risser and Bottoms 2014). Finally, including additional data sources beyond the technical ecosystem (e.g., recording the discussions during teacher training sessions, or gathering the teachers' perceptions about their learning experience) would significantly enrich the initial quantitative estimations reported in our study, as already illustrated by Leoste et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of community analytics (Klamma 2013;Jeong et al 2017) could contribute to guide further analyses of the Go-Lab community focusing on the teachers themselves, how they move from individual to collaborative interactions, and how these interactions develop over time (Imroz 2019). From a network analysis point of view, integrating social network analysis (Jan et al 2019;Saqr et al 2020), social learning analytics (Shum and Ferguson 2012), and cluster analysis could help us understand the social practices and the role that experts play in them (Martínez et al 2006;Risser and Bottoms 2014). Finally, including additional data sources beyond the technical ecosystem (e.g., recording the discussions during teacher training sessions, or gathering the teachers' perceptions about their learning experience) would significantly enrich the initial quantitative estimations reported in our study, as already illustrated by Leoste et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fincham et al (2018) used different social tie extraction methods and examined the influences on the structural and statistical properties of the networks; the results confirmed that social tie definitions play an important role in shaping the results. Saqr et al (2020) examined how different network configurations influence the reproducibility and robustness of centrality measures as indicators of CSCL learning. Therefore, researchers should be aware that relational ties can be built in varied ways, and the choices of measurements can influence results.…”
Section: Basic Rationale Of Using Sna In Csclmentioning
confidence: 99%
“…Diverse types of “actors” are involved in, such as learners, technologies, and activities; relations are built between these “actors”, which have critical influences on CSCL processes. Therefore, an underlying philosophy of CSCL is “relations matter” (Dado & Bodemer, 2017; Saqr et al., 2020; Wu & Nian, 2021). To understand CSCL, it is necessary to analyze characteristics of CSCL entities, the relations between them, and the mediating effect of these relations on CSCL processes and outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations